ANALISIS IMPLEMENTASI 6S (HOUSEKEEPING 5S DAN SAFETY) PADA AREA WAREHOUSE OPERATION PT. MMS - Achmad Zaki; Taqwanur Taqwanur; Nafia Ilhama Qurratu’aini (Media Mahardhika, 2023)
Presearchers use the analysis of the application of 5S and safety to find out before and after related to the arrangement and work safety system in PT. MMS Sidaorjo Regency. Implementation of this research using qualitative methods. The data used according to research takes from words, situations, actions and events. Here using the interview activity. Hthe results of the research that has been done, several conclusions can be drawn, namely for the implementation of 5S and Safety (job security). Seiri (Brief), Seiton (Neat), Seiso (Clean), Seiketsu (Rawat), Shitsuke (Hardworking), Safety (job security) has been fully implemented.